The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997000800011
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose ingestion causes opioid analgesia

Abstract: The intake of saccharin solutions for relatively long periods of time causes analgesia in rats, as measured in the hot-plate test, an experimental procedure involving supraspinal components. In order to investigate the effects of sweet substance intake on pain modulation using a different model, male albino Wistar rats weighing 180-200 g received either tap water or sucrose solutions (250 g/l) for 1 day or 14 days as their only source of liquid. Each rat consumed an average of 15.6 g sucrose/ day. Their tail w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 13 publications
(18 reference statements)
6
32
0
7
Order By: Relevance
“…Although the mechanisms underlying sucrose-induced analgesia in human infants and children is not fully established (Taddio et al, 2003;Gradin and Schollin, 2005), animal model studies suggest the involvement of the endogenous opioid system (Segato et al, 1997). For example, the effects of sucrose are abolished by the administration of the opiate receptor antagonists naloxone or naltrexone in rat pups (Blass et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms underlying sucrose-induced analgesia in human infants and children is not fully established (Taddio et al, 2003;Gradin and Schollin, 2005), animal model studies suggest the involvement of the endogenous opioid system (Segato et al, 1997). For example, the effects of sucrose are abolished by the administration of the opiate receptor antagonists naloxone or naltrexone in rat pups (Blass et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose-induced analgesia during infancy develops rapidly and persists for several minutes [57]. In addition, sucrose ingestion for a relatively long period of time produces analgesia [58,59]. Acute sucrose-induced analgesia is age-dependent that means it occurs mainly during the preweaning period in rats [57].…”
Section: Sweet Solution Analgesia In Animal Studiesmentioning
confidence: 99%
“…57,73,74 Results from a systematic review of the literature support using sucrose to provide pain relief to infants undergoing venous access. 75 As for the mechanism, some have suggested that sucrose works via the activation of endogenous opioids, 76 although others have not found support for this hypothesis. 77,78 Sucrose administration is typically done by dipping a pacifier into a solution or instilling it directly into the mouth with a syringe.…”
Section: Interventions For Young Infantsmentioning
confidence: 99%